CHILD PSYCHOLOGICAL DYNAMICS AS PERPETRATORS OF THEFT - Hardiyanti Rahmah; Husin; Sir Ahmad Rizhan; Abdul Rashid bin Abdul Aziz (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
. Child delinquency is an act that violates the norms or rules in society that is committed by children. Child delinquency is a social phenomenon caused by a form of social neglect which ultimately leads to deviant behavior or delinquency. But there are several factors that influence children to do these actions. This study aims to determine the psychological dynamics of children as perpetrators of theft, so they can handle or even prevent other children. This research uses a qualitative method, because this method can be used to explore and understand the meaning of a number of individuals or groups who are considered to have social or humanitarian problems. The results of this study indicate that children commit acts of theft because of a lack of attention from the family or even from their own parents to become a bad figure for their children. Likewise, the influence of peers who are naughty in association can also influence the behavior of children to become naughty. And a bad environment can influence children's behavior to be bad, because children tend to imitate what they see in their environment whether it's good or bad.